The Repair of Large Incisional Hernias - Knight, Irving A. (1968)
An old technique for the repair of incisional hernias, but with the use of Marlex mesh instead of fascia lata, was used in eight cases, with good results for the limited time the patients have been observed. The operation involves the use of a multifingered sheet of Marlex mesh, a material with characteristics that make it ideal for repair of large hernias.